THE EFFECT OF USING MOVIE TO OVERCOME LISTENING COMPREHENSION DIFFICULTIES OF JUNIOR HIGH SCHOOL STUDENTS - Manurung, Eva Talenta; Butar-Butar, Yeyen Nopriyanti; Simbolon, Desi Devi Vania (Transpublika Publisher, 2022)
The purpose of this research is to investigate the use of the media movie to the listening comprehension of the students. The method in this research is Classroom Action Research. The researchers conducted two cycles to measure the use of movie media in solving students’ listening comprehension problems. Participants in this research were students of class VIII-2 at SMP Negeri 4 Pematangsiantar. To collect the research data, researchers conducted tests that held on each cycle to see the development of students when studying the listening using media movie. Based on the results of research conducted by researchers, researchers found that students were helped in overcoming their limitations in listening to English using Media Movie. Thus, movie is one of the media that can be used to teach listening to students.